2010
DOI: 10.3382/ps.2010-00955
|View full text |Cite
|
Sign up to set email alerts
|

Beak condition and cage density determine abundance and spatial distribution of northern fowl mites, Ornithonyssus sylviarum, and chicken body lice, Menacanthus stramineus, on caged laying hens

Abstract: Adult White Leghorn hens (Hy-Line strain W-36) were inoculated with either northern fowl mites or chicken body lice, and the ectoparasite populations were monitored over periods of 9 to 16 wk. Two beak conditions (beak trimmed or beak intact) and 2 housing densities (1 or 2 hens per 25 × 31 cm suspended wire cage) were tested. Populations of both ectoparasites were at least 10 times lower on beak-intact hens compared with populations on beak-trimmed hens. Cage density did not influence mite numbers, but higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 44 publications
2
24
0
1
Order By: Relevance
“…Apparent confusion with similar mite species, primarily O. sylviarum which may cohabit with D. gallinae and pose similar problems for hen [7,9,32] and human [4,18,20-23,33] health, may also hamper positive identification and appropriate treatment of both species. Hence, the current work also makes comparison among these two mites for the benefit of the end user.…”
Section: Discussionmentioning
confidence: 99%
“…Apparent confusion with similar mite species, primarily O. sylviarum which may cohabit with D. gallinae and pose similar problems for hen [7,9,32] and human [4,18,20-23,33] health, may also hamper positive identification and appropriate treatment of both species. Hence, the current work also makes comparison among these two mites for the benefit of the end user.…”
Section: Discussionmentioning
confidence: 99%
“…If infestation with different kinds of parasites does not change dustbathing behavior, it would strengthen the hypothesis that dustbathing is not functionally related to the removal of ectoparasites. In addition, it is known that hens with an intact beak are able to reduce their ectoparasite loads (Mullens et al, 2010) via preening directed to the body areas that are most severely infested (Vezzoli et al, 2015b). However, to our knowledge there have been no studies evaluating the interactive effects of preening and dustbathing in beak-intact hens on ectoparasite loads.…”
Section: Measurementioning
confidence: 92%
“…In the present study, mite populations on cage-free hens occasionally tended to be higher early in infestation than those on hens in cages, but large or consistent 'density' effects on mites were not seen. Mullens et al (2010) showed that hens held in pairs per cage supported about twice as many lice as hens held singly in cages, presumably because crowded hens were less efficient in grooming. In the present study, no significant housing effects on CBL abundance emerged in any trial.…”
Section: Housingmentioning
confidence: 99%